Management Of Teacher Performance Improvement At SMK Negeri Tanjungpinang - Afriyadi Afriyadi; Ayu Wardani; Defa Muhammad Hafiz; Jhony Hasianus Sinaga; Risma Selvi Dewi (International Journal of Management Research and Economics, 2024)
This research aims to describe the efforts needed to enhance the performance of teachers at SMK Negeri 1 Tanjungpinang. Teachers' performance significantly impacts students' academic achievements and character formation. In the evolving dynamics of education, improving teachers' performance is not just a task but a necessity. The research focuses on aspects such as understanding performance management, performance planning, implementation, monitoring, assessment, and evaluation. The research method used is qualitative descriptive with data collection through interviews. The population of this study is 100 teachers with a sample of 2 informants.